Preclinical pharmacology of amphetamine: Implications for the treatment of neuropsychiatric disorders - Hutson, Peter H.; Tarazi, Frank I.; Madhoo, Manisha; Slawecki, Craig; Patkar, Ashwin A. (Pharmacology & therapeutics (Oxford), 2014)
The primary mechanism by which amphetamine exerts its neurobehavioral effects is through an enhancement of synaptic monoamine levels, which is mediated by interactions with monoamine transporters, storage, and metabolism. However, preclinical data are now emerging that support more widespread neurobiologic effects for amphetamine. This review describes preclinical evidence suggesting that direct interactions of amphetamine with monoamine systems, which results in increased synaptic monoamine availability, has downstream effects on nonmonoaminergic systems, including glutamate, endogenous opioid, endocannabinoid, and acetylcholine systems. Furthermore, evidence suggests that amphetamine can modulate synaptic plasticity through modulation of glutamatergic systems, intracellular signaling cascades, and neurotrophic factor activity. Functional activity of these systems is implicated in the regulation of neurobehavioral processes that include cognition, mood, motivated behavior/hedonic processes/addiction, and arousal. As such, the ability of amphetamine to influence the function of systems that mediate these processes suggests amphetamine-based agents may have utility in the treatment of psychiatric disorders in which these systems and processes are dysfunctional. Amphetamine-based agents are currently approved by the US Food and Drug Administration only for the treatment of attention-deficit/hyperactivity disorder and narcolepsy. Preclinical and clinical research for amphetamine-based pharmacotherapy for other psychiatric disease states is examined. This should encourage further research on the preclinical pharmacology of amphetamine and its implications for the treatment of neuropsychiatric disorders.